Intraoperative Fluoroscopy Decreases Magnitude and Incidence of Leg-Length Discrepancy Following Total Hip Arthroplasty - Christopher L. Blum, MD; Andrew J. Luzzi, MD; Jeremy S. Frederick, MD; H. John Cooper, MD; Roshan P. Shah, MD, JD; Jakub Tatka, MD; Jeffrey A. Geller, MD; Carl L. Herndon, MD (Arthroplasty Today)
Background: Leg-length discrepancy (LLD) can lead to patient dissatisfaction and decreased function after total hip arthroplasty (THA). This study examines the impact of intraoperative fluoroscopy on the magnitude and incidence of LLD after THA. Methods: Patients undergoing primary THA were identified and stratified into cohorts based on one out of 4 surgical approaches and intraoperative fluoroscopy use. The most recent 100 patients matching each cohort were included. Preoperative and postoperative LLD was assessed radiographically via an interteardrop reference line to lesser trochanter measurement.Magnitude of LLD and the proportion of patients in each cohort with LLD >5 mm, >10 mm, and 15 mm were analyzed. Results: Four hundred patients were stratified into 4 equal cohorts. Overall, THA done with fluoroscopy yielded fewer leg length discrepancies than THA done without fluoroscopy. The anterior-based muscle sparing (ABMS) approach with fluoroscopy had significantly less postoperative LLD than the posterior approach without fluoroscopy (3.4 vs 5.1 mm, P < .01) and the ABMS approach in the lateral position without fluoroscopy (3.4 vs 4.8 mm, P = .03). For LLD >5 mm, the ABMS approach with fluoroscopy cohort had significantly fewer patients compared to the ABMS approach without fluoroscopy (23 vs 41, P < .01). For LLD >10 mm, the ABMS approach with fluoroscopy cohort had significantly fewer patients compared to the posterior approach without fluoroscopy (2 vs 15, P < .01). For LLD >15 mm, relative to the posterior approach without fluoroscopy, all other cohorts had significantly fewer outliers (P < .02). Conclusions: This study supplies evidence that use of intraoperative fluoroscopy is likely beneficial in reducing the magnitude of LLD following THA and reducing the incidence of outlier LLDs >5 mm, >10 mm, and <15 mm.